PERANCANGAN SISTEM PENGELOLAAN PELANGGAN SEBAGAI STRATEGI BERTAHAN HIDUP CV NADYA SALON - Anggraini, Westi
A medium-sized MSME in Bekasi engaged in the beauty industry called CV Nadya Salon has been established since 1996. After temporarily closing due to the COVID-19 pandemic, CV Nadya Salon was never able to reach the 50% revenue target per month. CV Nadya Salon can not survive if the company do nothing. After further investigation, the decline in revenue occurred because many valueble customers of CV Nadya Salon did not comeback anymore and the company's inability to carry out proper retention efforts to keep its customers. For this reason, it is necessary to design a Customer Relationship Management (CRM) that is in accordance with the needs and readiness of CV Nadya Salon so that the company can survive. The research begins with an assessment of the readiness company's survival aspects with the Gamage framework to measure 10 aspects, infrastructure, materials, market knowledge, certification, management capability, brand name and development, distribution channels, and investment. Focus of the marketing strategy (acquisition or retention) will also be identified. Then the company's CRM readiness is measured through a comprehensive CRM audit system and the company's STP (segmenting, targeting, positioning) is identified. All data that has been obtained will be processed and used as the basis for designing CRM. Furthermore, the design of the CRM will be implemented to determine the effectiveness of its performance. From the results identification of survival aspects, CV Nadya Salon needs to develop the distribution channel aspect. It was found that the focus of the marketing strategy is retention, and the CRM component that must be developed is information management. So, the direction development SPP CV Nadya Salon is an information management process to support retention efforts through distribution channels that are in accordance with the company's STP. Based on these directions, a proposed CRM will be designed in the form of establishing a knowledge management system equipped with dashboard requirements. This research also uses a proposed system that has been designed by carrying out a promotional strategy through Whatsapp Blast to get win-back customer.